SISTEM SAPAAN BAHASA MELAYU BANGKA - Feri Pristiawan (﻿Kantor Bahasa Provinsi Bangka Belitung, 2013)
Bahasa memiliki peranan penting sebagai alat komunikasi di seluruh penjuru dunia dan kata sapaan menjadi salahsatu unsur utama guna mengawali proses komunikasi. Tulisan ini mengkaji penggunaan kata-kata sapaan yangsecara umum digunakan dalam bahasa Melayu Bangka. Pengkajian yang dilakukan berkaitan dengan sistemsapaan dalam situasi kekerabatan masyarakat Melayu Bangka, pola hubungan sistem kekerabatan masyarakatMelayu Bangka, dan penggunaan sapaan dalam masyarakat Melayu Bangka. Pengumpulan data menggunakanteknik wawancara, sedangkan analisis data menggunakan metode deskriptif. Dari hasil analisis, diketahui bahwapenggunaan kata sapaan bahasa Melayu Bangka memiliki kaitan dengan faktor kekerabatan, umur, keakraban,jabatan, status sosial, situasi, dan tujuan pembicaraan.Kata Kunci: bahasa, sapaan, sosiolinguistik, deskriptifAbstractLanguage has the important role as communication tool in all over the world, and greeting becomes one of mainelements to begin the communication process itself. This article analyses the commonly greeting spoken inBangkanese Malay language. The analysis hold relates to the greeting system in the kinship situation ofBangkanese Malay society, relationship pattern of kinship system of Bangkanese malay society, and the usage ofgreeting in Bangkanese Malay society. Data collection uses the interview technique while applying thedecsriptive method of data analysis to describe the content of research. From analysis result note that the usage ofgreeting in Bangkanese Malay language has correlation with community kinship, age, intimacy, position, socialstatus, situation, and purpose of discussion factors.